Peran Badan Pelindungan Pekerja Migran Indonesia (BP2MI) Dalam Upaya Perindungan Hukum Pra Penempatan Pekerja Migran Indonesia : (Studi di UPT BP2MI Mataram) - Adinda Rizka; Any Suryani Hamzah (Private Law, 2022)
Migrant worker is an alternative in order to minimize unemployment number in Indonesia. BP2MI is an agency who has responsibilities to protect Indonesian migrant worker in time of pre-placement, placement and post placement. The aims of this research are to know the role of BP2MI Mataram in the protection of migrant worker during pre-placement time and implementation of Government Regulation Number 90 of 2019 on BP2MI. This research is qualified as empirical legal research. From research result, it is shows that form of legal protection in pre-placement phase are administratively and technically. However, it implementation of migrant worker protection by BP2MI Mataram is delivered by pre-placement protection.